Encapsulation of Nanocrystals in Mannitol-Based Inhalable Microparticles via Spray-Drying: A Promising Strategy for Lung Delivery of Curcumin - Luca Casula; Emanuela Fabiola Craparo; Eleonora Lai; Cinzia Scialabba; Donatella Valenti; Michele Schlich; Chiara Sinico; Gennara Cavallaro; Francesco Lai (Pharmaceuticals)
Background/Objectives: Curcumin is well known for its great anti-inflammatory and antioxidant efficacy, representing a potential strategy for the treatment of respiratory disorders. However, several drawbacks, such as chemical instability, poor water solubility and rapid metabolism, result in low bioavailability, limiting its clinical applications. In this study, curcumin nanocrystals were incorporated into mannitol-based microparticles to obtain an inhalable dry powder. Methods: A curcumin nanosuspension was produced by wet-ball media milling and thoroughly characterized. Spray drying was then used to produce mannitol microparticles incorporating curcumin nanocrystals. In vitro release/dissolution tests were carried out in simulated lung fluids, and the aerosolization properties were evaluated using a Next-Generation Impactor (NGI, Apparatus E Ph. Eu.). Results: The incorporation of curcumin nanocrystals into mannitol-based microparticles influenced their morphological properties, such as geometric diameters, and flowability. Despite these changes, nebulization studies confirmed optimal MMAD values (<5 µm), while multi-step dissolution/release studies evidenced the influence of mannitol. Conclusions: The developed curcumin nanocrystals-loaded mannitol microparticles show promise as an inhalable treatment for respiratory diseases, combining effective aerodynamic properties with controlled drug release.